Abundant molecular gas and inefficient SF in intra-cluster regions of a ram pressure stripped tail. Issue Volume 10:Issue S309(2014) (9th February 2015) - Jáchym, P.; Sun, M.; Combes, F.; Cortese, L.; Kenney, J. D. P.
Abstract: For the first time in any ram pressure stripped galaxy, we detect large amounts of cold molecular gas in the X-ray bright, and star forming tail of ESO 137-001 in the Norma cluster. We find very low star formation efficiency in the stripped gas, similar to values found in the outer spiral disks where however molecular gas is mostly undetected. The results were recently published in Jáchym et al . (2014 ).